Encyclopaedia of physical education and sports Vol.2 The sociology of sports - Sharma, Bela Rani (ed); Kaushik, Vijaya (ed); Kaushik, Vijaya (Ed.) (New Delhi Sarup Book Publishers, 2012)
The sociology of sports